Influence of baseball training load on clinical reach tests and grip strength in collegiate baseball players - Pexa, B.; Ryan, E. D.; Blackburn, J. T.; Padua, D. A.; Garrison, J. C.; Myers, J. B. (Journal of Athletic Training, 2020)
Context: A baseball-specific training load may influence strength or glenohumeral range of motion, which are related to baseball injuries. Glenohumeral reach tests and grip strength are clinical assessments of shoulder range of motion and upper extremity strength, respectively. Objective: To examine changes in glenohumeral reach test performance and grip strength between dominant and nondominant limbs and high, moderate, and low baseball-specific training-load groups. Design: Repeated-measures study. Setting: University laboratory and satellite clinic. Patients or Other Participants: Collegiate baseball athletes (n = 18, age = 20.1 ± 1.3 years, height = 185.0 ± 6.5 cm, mass = 90.9 ± 10.2 kg). Main Outcome Measure(s): Participants performed overhead reach tests (OHRTs), behind-the-back reach tests (BBRTs), and grip strength assessments using the dominant and nondominant limbs every 4 weeks for 16 weeks. Percentage change scores were calculated between testing times. After each training session, participants provided their duration of baseball activity, throw count, and body-specific and arm-specific ratings of perceived exertion. We classified them in the high, moderate, or low training-load group based on each training-load variable: body-specific acute:chronic workload ratio (ACWR), arm-specific ACWR, body-specific cumulative load, and arm-specific cumulative load. Mixed models were used to compare training-load groups and limbs. Results: The arm-specific ACWR group demonstrated as main effect for OHRT (F = 7.70, P = .001), BBRT (F = 4.01, P = .029), and grip strength (F = 8.89, P < .001). For the OHRT, the moderate training-load group demonstrated a 10.8% greater increase than the high group (P = .004) and a 13.2% greater increase than the low group (P < .001). For the BBRT, the low training-load group had a 10.1% greater increase than the moderate group (P = .011). For grip strength, the low training-load group demonstrated a 12.1% greater increase than the high group (P = .006) and a 17.7% greater increase than the moderate group (P < .001). Conclusions: Arm-specific ACWR was related to changes in clinical assessments of range of motion and strength. Clinicians may use arm-specific ACWR to indicate when a baseball athlete's physical health is changing.